2015
DOI: 10.1615/interfacphenomheattransfer.2015014454
|View full text |Cite
|
Sign up to set email alerts
|

Recoil of Drops During Coalescence on Superhydrophobic Surfaces

Abstract: A numerical and experimental study has been carried out with a pair of water drops coalescing over a superhydrophobic surface. Initially, a stationary isolated drop (of given radius R1) in the sessile configuration is just touched by another drop (of radius R2), vertically in line with it, at zero speed. The solid substrate is a chemically treated, polished superhydrophobic surface made up of copper, for which the equilibrium contact angle for water was measured to be 150 •. The Bond number, considering the to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…The droplet impact on the already deposited sessile droplet (drop-on-drop) is also analyzed in a few works for a range of Weber numbers, the configurations are shown in parts (ii) and (iii) of Figure 1a. Gunjan et al 21 and Somwanshi et al 22 investigated the coalescence of droplets with a low Weber number of vertically aligned oncoming droplet on a superhydrophobic substrate (We < 1) and concluded that the difference in the surface energy is the driving force for the lift-off of the combined droplet after coalescence. Wang et al 23 reported various outcomes during the drop-on-drop impact, namely: complete rebound, coalescence, and partial coalescence.…”
Section: Dropletsmentioning
confidence: 99%
“…The droplet impact on the already deposited sessile droplet (drop-on-drop) is also analyzed in a few works for a range of Weber numbers, the configurations are shown in parts (ii) and (iii) of Figure 1a. Gunjan et al 21 and Somwanshi et al 22 investigated the coalescence of droplets with a low Weber number of vertically aligned oncoming droplet on a superhydrophobic substrate (We < 1) and concluded that the difference in the surface energy is the driving force for the lift-off of the combined droplet after coalescence. Wang et al 23 reported various outcomes during the drop-on-drop impact, namely: complete rebound, coalescence, and partial coalescence.…”
Section: Dropletsmentioning
confidence: 99%